E-learner success assesment model (E_LSAM) in higher education: Does it work? - Sulistiani, Dwi; Bashith, Abdul; Amin, Saiful (Edelweiss Applied Science and Technology, 2025)
In today’s digital age, the amount of available research literature is growing exponentially, the new normal era, after the COVID-19 pandemic, requires the world of education to carry out offline and online learning. Therefore, e-learner success remains an interesting topic to discuss. This research was conducted to map the factors, dimension, and mediating variable that determine the e-learner success in E-LSAM (E-Learner Success Assesment Model) model. The data is based on a survey method distributed to 1139 students from 12 State Islamic Higher Education Institutions (SIHEIs) in Indonesia. The collected data was then tested using Structural Equation Model (SEM) AMOS version 26. The results of this study indicate that the E-LSAM model is an effective assessment in measuring e-learner success. Variables that support the e-learner success are: self-efficacy, perceived enjoyment, subjective norm, image, perceived ease to use, service quality, social interaction, system quality, and diversity in assessment. The instructor dimension is the dimension that has the highest impact in achieving e-learner success, apart from that the system and course dimensions also provide support. Self-regulation, perceived usefulness, intention to continue using LMS (Learning Management System), attitude toward LMS, and learner satisfaction are important factors that directly and indirectly affect the learner success. LMS operation training needs to be held for instructors to improve e-learner success in SIHEIs.